2014
DOI: 10.1136/heartjnl-2013-305417
|View full text |Cite
|
Sign up to set email alerts
|

The dialysis procedure as a trigger for atrial fibrillation: new insights in the development of atrial fibrillation in dialysis patients

Abstract: This study provides insight in the exact timing of AF onset in relation to the dialysis procedure itself. In HD patients, AF occurred significantly more often on a dialysis day and especially during HD. These findings might help to elucidate some aspects of the pathophysiology of AF in dialysis patients and could facilitate early detection of AF in these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 29 publications
2
64
0
3
Order By: Relevance
“…AF was detected in 14 of 40 dialysis patients-11 receiving HD, 3 receiving peritoneal dialysis, and 9 without known AF (54). AF frequency was three-fold higher on dialysis days (P50.001) but did not differ with duration of the interdialytic interval.…”
Section: Dialysis As a Triggermentioning
confidence: 93%
“…AF was detected in 14 of 40 dialysis patients-11 receiving HD, 3 receiving peritoneal dialysis, and 9 without known AF (54). AF frequency was three-fold higher on dialysis days (P50.001) but did not differ with duration of the interdialytic interval.…”
Section: Dialysis As a Triggermentioning
confidence: 93%
“…Hemodialysis favors the initiation of AF through rapid shifts in fluid and electrolytes (potassium), and episodes of AF are common during hemodialysis. 20 Although hemodialysis-induced AF may contribute to the increase in stroke risk observed in those initiating dialysis, it must be acknowledged that patients are anticoagulated during their dialysis sessions. Therefore, it is possible that hemodialysis-related AF may carry a lower risk of stroke than AF in the general population.…”
Section: Risk Factors For Strokementioning
confidence: 99%
“…20 Buiten and associates reported that the risk of atrial fibrillation was 7-fold higher during than before dialysis, implicating intravascular depletion as a potential mechanism. They also observed a correlation with dialysate potassium concentration, suggesting electrolyte shifts as a possible cause.…”
Section: Discussionmentioning
confidence: 99%